BA 224 - Human Resource Management - Linn Benton Virtual College (2018)
This course explores the basics of human resource management including selection and hiring, performance appraisal, compensation, staff planning and job analysis. This course also addresses current HR issues such as job search in a difficult economy, discrimination and harassment, workplace violence and on-the-job drug abuse.